Offering extended use of the combined contraceptive pill: a survey of specialist family planning services - Sauer U; Mann S; Brima N; Stephenson J (Dove Medical Press, 2013)
Ulrike Sauer,1 Sue Mann,2 Nataliya Brima,3 Judith Stephenson21Reproductive and Sexual Health, Enfield Community Service, Enfield, 2Sexual and Reproductive Health Research Group, Institute for Women’s Health, 3Research Department of Infection and Population Health, University College London, London, UKBackground: The purpose of this study was to determine attitudes to, and provision of, extended regimens for taking the combined oral contraceptive pill (COC) by specialist contraception practitioners from three contrasting specialist contraception services in London.Methods: An online cross-sectional survey was administered to all doctors and nurses, who counsel, provide, or prescribe the oral contraceptive pill at each clinic.Results: A total of 105 clinicians received the questionnaire and 67 (64%) responded. Only one of three clinics initiated and maintained guidelines for extended COC use. In that service, 60% of staff prescribing COC advised more than 50% of patients regarding alternative COC regimens. In the other two services, this was discussed with 20% and 6% of patients, respectively (P < 0.001). The reasons for prescribing extended use included cyclic headaches, menorrhagia, patient request, menstrual-related cramps, and endometriosis, and did not differ between the three different settings. The most common extended regimens were 63 pills or continuous use until bleeding occurs, followed by a hormone-free interval. Concerns highlighted by providers and patients were “unhealthy not to have a monthly bleed”, “future fertility”, and “breakthrough bleeding”. Such comments highlight the need for further information for providers and patients.Conclusion: There is growing evidence, backed by national guidance, about extended COC use, but routine provision of this information is patchy and varies ten-fold, even within specialist family planning services. Targeted training, use of service guidelines, and implementation research will be needed to extend patient choice of different COC regimens and change clinical practice.Keywords: contraception, hormone-free interval, continuous combined contraception, extended pill use, counseling